PERSEPSI PENGUNJUNG TERHADAP DESA WISATA LEBAKMUNCANG (Suatu Kasus Desa Wisata Lebakmuncang, Kecamatan Ciwidey, Kabupaten Bandung) - Shintiya Devi Siregar; Endah Djuwendah; Elly Rasmikayati; Sulistyodewi Nur Wiyono (Universitas Galuh Ciamis, 2020)
Lebakmuncang Tourism Village is a village that has natural potential, cultural potential, and human resources potential to be developed into tourist attractions. However, in the development of this tourist village has a fluctuating number of visitors. The research to analyzes visitor's perceptions of the attractiveness of Lebakmuncang Tourism Village. Visitors' perceptions are viewed from the concept of 4A tourism namely Attractiveness, Amenity, Accessibility, and Ancilliary. This research was conducted in the Lebakmuncang Tourism Village, Ciwidey District, Bandung Regency, West Java. The research design used a descriptive quantitative design with survey methods. Data collection uses interviews, questionnaires, observations, and literature study. The sample selection of visitors uses purposive sampling with the Slovin formula and produces 50 respondents. The results showed that the visitor's perception of the attractiveness of the Lebakmuncang Tourism Village was considered very good on Attraction and Ancillary and good on Amenity and Accessibility.